Using push-pull winescape attributes to model Australian wine tourist segmentation - Quintal, Vanessa; Thomas, B.; Phau, Ian; Soldat, Z. (Emerald Group Publishing, 2017)
Purpose: The study aims to introduce a comprehensive segmentation instrument that incorporates the push–pull winescape attributes, providing a new perspective of the wine tourist profile and explaining their behavioural intentions in the Australian winescape. Design/methodology/ap proach: A literature review, focus groups and expert panels generated an extensive list of push–pull winescape attributes. Pen-and-paper surveys conveniently sampled 739 wine tourists at three wineries across three wine regions in Australia. Adopting push–pull winescape attributes as the segmentation base, cluster analysis identified four segments, namely, inspireds, self-drivens, market-drivens and inerts, and their behavioural intentions were examined. Findings: Inspireds demonstrate both self- and market-motivation. Self-drivens exhibit self-motivation but limited market-motivation, whereas Market-drivens characterise market-motivation but limited self-motivation. Inerts are limited in both market- and self-motivations. At the Swan Valley, all four segments were identified, with Inspireds being the most willing to revisit and recommend to others and Inerts, the least willing. At the Barossa Valley, only two segments emerged. Again, Inspireds and Inerts were the most and least willing to revisit and recommend to others respectively. Finally, at the Yarra Valley, three segments were identified. Market-drivens were most willing to revisit and recommend to others, followed by self-drivens and lastly, by inerts. Research limitations/implications: A comprehensive push–pull winescape segmentation base of wine tourists is introduced, which provides a more sophisticated profile of wine tourist segments than otherwise would be attained with conventional measures. Practical implications: New insights into who the wine tourist is and what it is they seek from the winescape are vital to smaller wine producers whose best access to the domestic retail and export markets is through direct selling at the cellar door. Originality/value: The empirically tested 18-item push–pull winescape instrument presents a comprehensive segmentation approach, which profiles wine tourists and predicts their behavioural intentions based on an extensive investigation of push–pull winescape attributes.